2023
DOI: 10.1039/d3nr00435j
|View full text |Cite
|
Sign up to set email alerts
|

Results of an interlaboratory comparison for characterization of Pt nanoparticles using single-particle ICP-TOFMS

Lyndsey Hendriks,
Robert Brünjes,
Sara Taskula
et al.

Abstract: This study describes an interlaboratory comparison (ILC) among nine (9) laboratories to evaluate and validate the standard operation procedure for single-particle (sp) ICP-TOFMS developed within the context of the Horizon...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The characterization of bimetallic Pt-Pd NPs requires diverse techniques, from conventional methods such as scanning/transmission electron microscopy (S/TEM) and dynamic light scattering (DLS) to advanced ones such as single-particle inductively coupled plasma mass spectrometry (spICP-MS) and single-particle time-of-flight ICP-MS (spTOF-ICP-MS) [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of bimetallic Pt-Pd NPs requires diverse techniques, from conventional methods such as scanning/transmission electron microscopy (S/TEM) and dynamic light scattering (DLS) to advanced ones such as single-particle inductively coupled plasma mass spectrometry (spICP-MS) and single-particle time-of-flight ICP-MS (spTOF-ICP-MS) [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important in new fields of testing, where analytical capabilities are not yet fully established. As the determination of NPs is an example of such a situation, we report the interlaboratory comparison (ILC) organised by a group of researchers 30 within the framework of the Horizon 2020 project ACEnano. The aim of the study was to validate a standard operating procedure, based on spICP-TOF-MS for the characterisation of Pt NPs .…”
Section: Metrology Interlaboratory Studies Reference Materials and Re...mentioning
confidence: 99%
“…8–15 To date, many spICP-TOFMS studies rely on manufacturer-provided software to identify particle-derived signals, quantify element mass amounts per particle, and determine particle number concentrations (PNCs). While these software can be fit for purpose, 16 we have found that current software options are often not flexible enough for users to adapt analysis procedures in accordance with the newest research findings or measurement approaches. For this reason, over the last several years, we have developed and extensively tested an in-house spICP-TOFMS data analysis software called the “time-of-flight single-particle investigator” or “TOF-SPI.” Our software is one of a growing number of free-use spICP-TOFMS data analysis software currently available.…”
Section: Introductionmentioning
confidence: 99%